Sejumlah Faktor yang Berhubungan dengan Pemberian Vitamin A pada Balita - Hanapi, Sunarti; Nuryani, Nuryani; Ahmad, Rahmawaty (Gorontalo Journal of Public Health, 2019)
Based on Indonesian Basic Health Research 2018Vitamin A capsule coverage for children 6-59 months reached 53.1%. Based on Department of Health Gorontalo district Vitamin A capsule coverage in work area of Asparaga community health center reached 80%. The research aims at investigating association of giving vitamin A toward toddler. This research used observational analytic method with cross sectional study approach. This research was conducted in February until April with total of samples were 262 children  6-59 mount and respondents were toddler mother. The technique of collecting samples was using purposive sampling technique and the technique of data collection was using questionnaire. The technique of data analysis was chi square test. The findings reseacrh was found that the giving of vitamin A on toddler was 126 (48,1%) and not giving vitamin A was 136 (51,9%) toddlers, low mothers knowledge 63,4%, active cadre 28,2%, active participation toddlers 5,0%. Base on analysis bivariate indicated that sufficient knowledge of mothers 67,7% of the toddlers were given vitamin A and chi square test showed knowledge of p value = 0,000, the role of active cadres 82,4% of the toddlers were given vitamin A with p value = 0,000 and the activity of toddlers visiting community health center / Posyandu 100% of the toddlers were given vitamin A with p value = 0,000. It was concluded that the mothers knowledge factor, the role of cadres and the activity of toddlers visiting Community Health Center and Posyandu were related to the provision of viramin A in the toddlers. It was recommended for mothers of toddlers to explore more information regarding the importance of providing vitamin A to toddlers, and to be active partisipation in Community Health Center / Posyandu activities.Berdasarkan hasil Riskesdas 2018 cakupan kapsul vitamin A pada anak 6-59 bulan mencapai 53,1%. Berdasarkan data Dinas Kesehatan Kabupaten Gorontalo cakupan pemberian vitamin A di Wilayah Kerja Puskesmas Asparaga mencapai 80%. Tujuan dalam penelitian ini untuk mengetahui sejumlah faktor yang berhubungan dengan pemberian vitamin A pada balita. Penelitian ini menggunakan metode observasional analitik dengan rancangan cross sectional study. Penelitian ini dilakukan pada Februari sampai April dengan jumlah sampel 262 balita umur 6-59 bulan dengan ibu balita sebagai responden. Pengambilan sampel dengan tekhnik purvosive sampling dan pengumpulan data dengan menggunakan kuesioner, analisis menggunaka chi square test. Hasil penelitian didapatkan pemberian vitamin A pada balita sebanyak 126 (48,1%) dan tidak diberikan vitamin A sebanyak 136 (51,9%) balita, pengetahuan ibu kurang 63,4%, keaktifan kader 28,2%, keaktifan kunjungan balita 5,0%. Berdasarkan hasil uji bivariat menunjukkan pengetahuan ibu cukup 67,7% anak balita diberikan vitamin A chi square  test menunjukkan pengetahuan  p value = 0,000, peran kader aktif 82,4% balita diberikan vitamin A dengan p value = 0,000, dan keaktifan kunjungan balita ke Puskesmas / Posyandu 100% balita diberikan vitamin A dengan p value = 0,000 berhubungan dengan pemberian vitamin A pada balita. Disimpulkan bahwa faktor pengetahuan ibu, peran kader dan keaktifan kunjungan balita ke Puskesmas dan Posyandu berhubungan dengan pemberian viramin A pada balita. Disarankan kepada ibu balita agar lebih menggali informasi terkait pentingnya pemberian vitamin A pada balita, serta aktif dalam kegiatan Puskesmas / Posyandu.